The Politics of LGBT Rights in Latin America and the Caribbean: Research Agendas - Corrales, Javier (European Review of Latin American and Caribbean Studies, 2015)
LGBT rights have expanded unevenly across Latin America and the Caribbean. Recent scholarship has been able to explain some of the reasons for this unevenness. But new and old questions remain unaddressed. This article suggests areas for further research. Resumen: Los derechos LGBT en la política de América Latina y el Caribe: Agendas para la investigación Los derechos LGBT han proliferado en América Latina y el Caribe de modo disparejo. Varios estudios académicos recientes han logrado explicar las razones de dicho crecimiento disparejo. Sin embargo, existen todavía preguntas sin responder al igual que nuevas preguntas por contestar. Este artículo sugiere algunas áreas que ameritan más investigación.